Structural effects of intra-articular TGF-β1 in moderate to advanced knee osteoarthritis: MRI-based assessment in a randomized controlled trial - A. Guermazi; G. Kalsi; J. Niu; M. D. Crema; R. O. Copeland; A. Orlando; M. J. Noh; F. W. Roemer (BMC Musculoskeletal Disorders, 2017)
Abstract Background To determine effects of allogeneic human chondrocytes expressing TGF-β1 (TG-C) on structural progression of MRI features of knee osteoarthritis over a 1 year period. Methods This phase II randomized controlled trial of TG-C included patients with moderate to advanced osteoarthritis. Patients were randomized to receive an intraarticular 3:1 mixture of non-transduced allogeneic human chondrocytes and TG-C or placebo. 3 T MRI was acquired for all patients at baseline and follow-up (3, 6 and 12 months). MRIs were assessed using the WORMS system including cartilage damage, bone marrow lesions (BMLs), meniscal damage/extrusion, Hoffa-, effusion-synovitis, and osteophytes. Analyses were performed on a whole knee level, compartmental level, and subregional level. Binary logistic regression with Generalized Estimating Equation was used to compare risks of progression, adjusting for baseline age and gender. Mann − Whitney − Wilcoxon tests were used to assess differences for continuous variables. Results Fifty-seven Patients were included in the TG-C group and 29 in the placebo group. At 12 months, knees in the TG-C group showed less progression of cartilage damage compared to placebo on a whole knee level (34.6% vs. 47.9%; adjusted RR 0.7, 95%CI [0.5–1.1], p = 0.077). Less progression of Hoffa-synovitis and effusion-synovitis was observed in the TG-C group compared to placebo (9.6% vs. 21.1%, adjusted RR 0.5, 95%CI [0.2,1.2], p = 0.115). No statistically significant differences were seen for BMLs, meniscal damage and osteophytes. Conclusions Intraarticular treatment with TG-C showed fewer patients in the treated group with progression in structural OA features and other MRI-defined inflammatory markers such as Hoffa-synovitis and effusion-synovitis. However, no differences were observed in regard to progression of BMLs and meniscal damage, or hypertrophic osteophyte formation. Trial registration NCT01221441 .Registered 13th October, 2010